1999
DOI: 10.1139/z99-172
|View full text |Cite
|
Sign up to set email alerts
|

Comparing bird assemblages in successional black spruce stands originating from fire and logging

Abstract: Comparisons of the effects of logging and fire as disturbance agents on the composition of bird assemblages in boreal ecosystems are still lacking or are limited to the short-term impacts of clear-cutting. In Quebec, where the boreal forest is largely dominated by black spruce (Picea mariana (Mill.) B.S.P.) stands, we surveyed 140 point-count stations in 3 postlogging and 4 postfire development stages determined according to the height of the regenerating spruce trees. Species richness did not vary among fores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
61
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(82 citation statements)
references
References 27 publications
18
61
3
Order By: Relevance
“…While we are unaware of other studies of invertebrates in response to disturbance regime, north American studies of birds (Schulte and Niemi, 1998;Hobson and Schieck, 1999;Imbeau et al, 1999;Simon et al, 2002a) and small mammals (Simon et al, 2002b) all identified some differences between logged and naturally regenerated populations. Structural attributes such as presence of snags were important for birds (Schulte and Niemi, 1998;Imbeau et al, 1999), but are less likely to impact litter-dwelling invertebrates.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…While we are unaware of other studies of invertebrates in response to disturbance regime, north American studies of birds (Schulte and Niemi, 1998;Hobson and Schieck, 1999;Imbeau et al, 1999;Simon et al, 2002a) and small mammals (Simon et al, 2002b) all identified some differences between logged and naturally regenerated populations. Structural attributes such as presence of snags were important for birds (Schulte and Niemi, 1998;Imbeau et al, 1999), but are less likely to impact litter-dwelling invertebrates.…”
Section: Discussionmentioning
confidence: 93%
“…Structural attributes such as presence of snags were important for birds (Schulte and Niemi, 1998;Imbeau et al, 1999), but are less likely to impact litter-dwelling invertebrates. Red-backed voles (Simon et al, 2002b) were thought to be impacted by high availability of coarse woody debris (CWD) in recently clearcut sites.…”
Section: Discussionmentioning
confidence: 99%
“…However, few species exhibited consistent differences in both age classes, suggesting that harvest alters species composition, but that its impacts vary with successional age (e.g., Schieck 1999, Schieck andSong 2006). Several other studies in boreal forests have reported greater compositional dissimilarities between burned and harvested sites immediately following disturbance than at later successional stages (Hobson and Schieck 1999, Imbeau et al 1999, Schieck and Hobson 2000, Morissette et al 2002, Hannon and Drapeau 2005. Although we did not find this, it is also important to note that the midregenerating harvested forests in our study would have been affected by harvest practises that occurred before widespread adoption of efforts to emulate natural disturbance (see Drapeau et al 2000).…”
Section: Discussionmentioning
confidence: 92%
“…Several studies suggest that some bird species found in naturally disturbed forest stands are significantly less abundant in postharvest stands of similar types and ages, especially in the earliest successional stages but also several decades after harvest (e.g., Schulte and Niemi 1998, Hannon 1999, Imbeau et al 1999, Simon et al 2002. However, others find little difference for most species (e.g., Lemelin et al 2007, Börger and Nudds 2014, Rempel et al 2016.…”
Section: Introductionmentioning
confidence: 99%
“…These initial differences can have significant implications for biotic communities, including plants (Carleton and MacLellan, 1994;Ehnes and Shay, 1995;Bradbury, 2002), birds (Schulte and Niemi, 1998;Hobson and Schieck, 1999;Imbeau et al, 1999), arthropods (Buddle et al, 2000) and small mammals (Simon et al, 2002). However, although some differences between burned and logged stands persist through time, the magnitude of differences generally diminish as snags in burned stands fall and as vegetation becomes dominated by the new cohort of trees.…”
Section: Introductionmentioning
confidence: 99%